Embedded entrepreneurship market, culture, and micro-business in insular Southeast Asia - Bråten, Eldar; Rudie, Ingrid (Social sciences in Asia,, 2013)
"Examines the importance of cultural meaning in the creation and utilization of economic value. Based on case-studies from Thailand, Malaysia, Singapore and Indonesia, the authors demonstrate that micro-scale entrepreneurship is intertwined with prevailing conceptions, moralities and habituations in the entrepreneurs' social milieu. More specifically, the volume argues that meaning-making is integral to economic opportunity; that economic actors' market agency is shaped by cultural experiences; that entrepreneurs' prototypical "individualism" is socially contingent; and that cultural meanings channel economic value among economic and social domains. Addressing core questions about "embedding", the authors suggest theoretical convergences between economic anthropology and economic sociology"--